Assessing Costs and Benefits of Measures to Achieve Good Environmental Status in European Regional Seas: Challenges, Opportunities, and Lessons Learnt - Börger, Tobias; Broszeit, Stefanie; Ahtiainen, Heini; Atkins, Jonathan P.; Burdon, Daryl; Luisetti, Tiziana; Murillas, Arantza; Oinonen, Soile; Paltriguera, Lucille; Roberts, Louise; Uyarra, Maria C.; Austen, Melanie C. (Frontiers in Marine Science, 2016)
The EU Marine Strategy Framework Directive (MSFD) requires Member States to assess the costs and benefits of Programmes of Measures (PoMs) put in place to ensure that European marine waters achieve Good Environmental Status by 2020. An interdisciplinary approach is needed to carry out such an assessment whereby economic analysis is used to evaluate the outputs from ecological analysis that determines the expected effects of such management measures. This paper applies and tests an existing six-step approach to assess costs and benefits of management measures with potential to support the overall goal of the MSFD and discusses a range of ecological and economic analytical tools applicable to this task. Environmental cost-benefit analyses are considered for selected PoMs in three European case studies: Baltic Sea (Finland), East Coast Marine Plan area (UK) and the Bay of Biscay (Spain). These contrasting case studies are used to investigate the application of environmental cost-benefit analysis including the challenges, opportunities and lessons learnt from using this approach. This paper demonstrates that there are opportunities in applying the six-step environmental cost-benefit analysis framework presented to assess the impact of PoMs. However, given demonstrated limitations of knowledge and data availability, application of other economic techniques should also be considered (although not applied here) to complement the more formal environmental cost-benefit analysis approach.